Detection and isolation of flavonoid and aromatic acid from Cynara scolymus different parts cultivated in iraq - Ajeel, Zaineb H.; N. Hamad, Maha (Iraqi Journal of Pharmaceutical Sciences, 2020)
The target of this study was to study the natural phytochemical components of the head (capsule) of Cynara scolymus cultivated in Iraq. The head (capsule) of plant was extracted by maceration in70% ethanol for 72 hours, and fractioned by hexane, chloroform and ethyl acetate. Preliminary qualitative phytochemical screening was performed on the ethyl acetate fraction for capsule was revealed the presence of flavonoid and aromatic acids. These were examined by (high -performance liquid chromatography) (HPLC diodarray), (high- performance thin-layer chromatography)(HPTLC).Flavonoids were isolated by preparative layer chromatography and aromatic acid was isolated by preparative high-performance liquid chromatography HPLC from the ethyl acetate fraction of capsule.Then identified by High Performance Thin Layer Chromatography HPTLC, High performance liquid chromatography HPLC diode array , ultraviolet diode array UV-diode array and Liquid Chromatography /Mass Spectroscopy LC/MS. The chloroform fraction from the capsule was evaluated by Gas Chromatography//Mass Spectrometer(GC/MS). The different chromatographic and spectroscopic techniques revealed the presence of luteolin, apigenin and cinnamic acid in capsule of Cynara scolymus, also 9-octadecanoic acid (oleic acid), Oxalic acid, allyl tetradecyl ester, limonene, in chloroform of Cynara scolymus.The results of the current study proved the presence of luleolin, apigenin,   and cinnamic acid in the ethyl acetate fraction of Cynara scolymus capsule.